MICROBIOLOGICAL EVALUATION OF THE SOIL IN IRRIGATED AREA WITH EFFLUENT POND STABILIZATION - BURBARELLI, RODRIGO C.; PIRES, MARTA S. GUILHERME; FILHO, BRUNO CORAUCCI; GUIMARÃES, JOSÉ ROBERTO; SIVIERO, ANTONIO ROBERTO (Revista Brasileira de Engenharia de Biossistemas, 2009)
This study evaluated the influence of application of pond effluent anaerobic stabilization in the soil andchanges in its microbial flora. Analysis were performed microbiological indicators of pollution and somephysico-chemical soil. The effluent of stabilization pond was applied to the soil in two ways, directly andalso after receiving the application of chlorine for the removal of microorganisms. The applicationtechnique used was a shallow grooves, as a form of post-treatment of effluent. Aimed to the agriculturalreuse of effluent, ie the use of irrigation water and nutrients present in the effluent, mainly nitrogen andphosphorus by maize (Zea mays). The microbiological parameters were monitored in soil fungi andtotal heterotrophic bacteria or total and physical-chemical parameters were pH at the beginning andend of the experiment and soil moisture collected. The data collected during the development of theproject were compared with the rates established by law and health aspects. The results of this studyrecommend the disinfection of effluent for use as irrigation or reuse